CMS physics technical design report, volume II: Physics performance - (:unkn) unknown (IOP PUBLISHING LTD, 2007)
CMS is a general purpose experiment, designed to study the physics of pp collisions at 14 TeV at the Large Hadron Collider ( LHC). It currently involves more than 2000 physicists from more than 150 institutes and 37 countries. The LHC will provide extraordinary opportunities for particle physics based on its unprecedented collision energy and luminosity when it begins operation in 2007. The principal aim of this report is to present the strategy of CMS to explore the rich physics programme offered by the LHC. This volume demonstrates the physics capability of the CMS experiment. The prime goals of CMS are to explore physics at the TeV scale and to study the mechanism of electroweak symmetry breaking - through the discovery of the Higgs particle or otherwise. To carry out this task, CMS must be prepared to search for new particles, such as the Higgs boson or supersymmetric partners of the Standard Model particles, from the start- up of the LHC since new physics at the TeV scale may manifest itself with modest data samples of the order of a few fb(-1) or less. The analysis tools that have been developed are applied to study in great detail and with all the methodology of performing an analysis on CMS data specific benchmark processes upon which to gauge the performance of CMS. These processes cover several Higgs boson decay channels, the production and decay of new particles such as Z' and supersymmetric particles, B-s production and processes in heavy ion collisions. The simulation of these benchmark processes includes subtle effects such as possible detector miscalibration and misalignment. Besides these benchmark processes, the physics reach of CMS is studied for a large number of signatures arising in the Standard Model and also in theories beyond the Standard Model for integrated luminosities ranging from 1 fb(-1) to 30 fb(-1). The Standard Model processes include QCD, B-physics, diffraction, detailed studies of the top quark properties, and electroweak physics topics such as the W and Z(0) boson properties. The production and decay of the Higgs particle is studied for many observable decays, and the precision with which the Higgs boson properties can be derived is determined. About ten different supersymmetry benchmark points are analysed using full simulation. The CMS discovery reach is evaluated in the SUSY parameter space covering a large variety of decay signatures. Furthermore, the discovery reach for a plethora of alternative models for new physics is explored, notably extra dimensions, new vector boson high mass states, little Higgs models, technicolour and others. Methods to discriminate between models have been investigated. This report is organized as follows. Chapter 1, the Introduction, describes the context of this document. Chapters 2-6 describe examples of full analyses, with photons, electrons, muons, jets, missing E-T, B-mesons and tau's, and for quarkonia in heavy ion collisions. Chapters 7-15 describe the physics reach for Standard Model processes, Higgs discovery and searches for new physics beyond the Standard Model.
Keywords: HIGGS-BOSON PRODUCTION; TO-LEADING-ORDER; PRODUCTION CROSS-SECTION; LARGE TRANSVERSE-MOMENTUM; HADRONIC DECAY WIDTH; ELECTROWEAK SYMMETRY-BREAKING; HIGH-PRECISION PREDICTIONS; NEUTRAL-CURRENT PRODUCTION; DEEP-INELASTIC SCATTERING; QED RADIATIVE-CORRECTIONS